Pembuatan Peta Tingkat Bahaya Erosi Daerah Pengaliran Sungai Way Sulan Lampung Selatan - Roslina Jayanti; Suprapto Suprapto (Jurnal Ilmiah Teknik Pertanian - TekTan, 2013)
Erosion potential map (TBE) is a thematic map that can be used for various purposes, especially with regard to the management of land resources. As long as the map is not yet available Erosion potential Way Sulan Watershed South Lampung regency in digital form that is created using ArcGIS 9.3. Creating maps Erosion potential is intended to provide information about the Regional Erosion potential At River Way Sulan. The Digital Map is created by a projection coordinate transformation step Maps South Lampung District , Land Cover Map, Map Conditions Slope, and map making rain erosivity index, then specify limits Watershed Way Sulan based network of rivers and topography. The next step overlaying of 4 (four) of the map and perform value calculation Erosion potential and Erosion Hazard Class. Overlay Map of R, K, LS and CP resulted in a Land Unit Map with land unit number 1 to 232 with erosion hazard classes different. Keywords: erosion potential map, erosion hazard class, ArcGIS 9.3